Tectonic and radioactivity impacts of U-238 on groundwater-based drinking water at Gosa and Lugbe areas of Abuja, North Central Nigeria - Maxwell, Omeje (Taylor and Francis Ltd., 2015)
Tectonic contribution of activity level of U-238 in groundwater-based drinking water in Gosa and Lugbe areas of Abuja was measured using inductively coupled plasma mass spectrometry (ICP-MS). The highest activity level of 2736 mu Bq L-1 reported in Lugbe borehole, whereas the lowest value of 443 mu Bq L-1 reported at Gosa borehole. The inhabitants permanently used water from the boreholes for daily consumption. The group receives 5.55 x 10(-5) mSv of the annual collective effective dose due to U-238 in drinking water. The radiological risks of U-238 in the water samples were found to be low, typically in magnitude of 10(-7) with cancer mortality value of 1.03 x 10(-7) and morbidity value of 1.57 x 10(-7). The chemical toxicity risk of U-238 in drinking water over a lifetime consumption has a mean value of 4.0 x 10(-3) g kg(-1) day(-1). It could be that the human risk due to U-238 content in groundwater supplies from ingestion may likely be the chemical toxicity of U-238 as a heavy metal rather than radiological risk. Significantly, Lugbe subsurface may have developed some fractions of granitic strata that contributed to the distribution of radioactive of U-238 in tectonically weak zones.